Diversity of Fish Types and Water Quality in the Waters of Curug Gumawang, Curuggoong Village, Padarincang District, Serang-Banten District - Hermawan Hermawan (CV Projurnal Mitra Publikasi, 2025)
This research was carried out in the Gumawang Waterfall Area in Padarincang Village, Padarincang District, Serang-Banten Regency. The research was carried out to determine the diversity of fish species found in the Gumawang Waterfall. The results of this research were that 7 types of fish were obtained, including tilapia, goldfish, wader, catfish, eel, chana and sili fish. The most abundant fish in the Gumawang waterfall area is the wader fish with a total of 35 fish. Fishing is carried out at 3 points. The fish species diversity index value at Curug Gumawang was 1.523840153, this result shows that it is in the